2001
DOI: 10.1007/s004210000321
|View full text |Cite
|
Sign up to set email alerts
|

Mechanomyogram and force relationship during voluntary isometric ramp contractions of the biceps brachii muscle

Abstract: The aim of the present study was to examine the non-stationary mechanomyogram (MMG) during voluntary isometric ramp contractions of the biceps brachii muscles using the short-time Fourier transform, and to obtain more detailed information on the motor unit (MU) activation strategy underlying in the continuous MMG/force relationship. The subjects were asked to exert ramp contractions from 5% to 80% of the maximal voluntary contraction (MVC) at a constant rate of 10% MVC/s. The root mean squared (RMS) amplitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
145
4
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(160 citation statements)
references
References 22 publications
(41 reference statements)
9
145
4
2
Order By: Relevance
“…The amplitude of the MMG signal is determined by the number of active motor units and their firing rates (Orizio, 1993;Orizio et al, 2003), and although not directly verified (Akataki et al, 2003), it has been suggested that the MMG frequency content qualitatively reflects the global firing rate of the unfused activated motor units (Akataki et al, 2001;Bichler, 2000;Bichler & Celichowski, 2001;Orizio, 1993;Orizio et al, 2003). Thus, examination of the MMG amplitude and mean power frequency vs. isometric torque relationships may provide information regarding the unique motor unit activation strategies (recruitment and firing rate) …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The amplitude of the MMG signal is determined by the number of active motor units and their firing rates (Orizio, 1993;Orizio et al, 2003), and although not directly verified (Akataki et al, 2003), it has been suggested that the MMG frequency content qualitatively reflects the global firing rate of the unfused activated motor units (Akataki et al, 2001;Bichler, 2000;Bichler & Celichowski, 2001;Orizio, 1993;Orizio et al, 2003). Thus, examination of the MMG amplitude and mean power frequency vs. isometric torque relationships may provide information regarding the unique motor unit activation strategies (recruitment and firing rate) …”
Section: Discussionmentioning
confidence: 99%
“…For the biceps brachii, several recent studies have reported increases in both MMG amplitude and MMG mean power frequency with submaximal isometric torque (Akataki, Mita, Watakabe, & Itoh, 2001;Akataki et al, 2003;Beck et al, 2004;Orizio et al, 1989;. At torque levels ≥ 60-80% MVC, however, MMG amplitude for the biceps brachii plateaus or decreases (Akataki et al, 2001;Beck et al, 2004;Orizio et al, 1989;.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Isometric contraction was employed to measure the force (Neering et al, 1991;Akataki et al, 1996;Akataki et al, 2001;Alves and Chau, 2008;Krueger et al, 2013).…”
Section: Protocolmentioning
confidence: 99%
“…MMG is used in many applications, including: prostheses control (Orizio et al, 2003); indication of muscle activation degree (Scheeren et al, 2010); monitoring of muscle fatigue (Orizio et al, 2003;Tarata, 2003); neuromuscular diseases diagnosis (Hu et al, 2007); obtainment of signals for the study of muscle strength gradation mechanisms (Akataki et al, 2001;Matta et al, 2005;Madeleine et al, 2001;Nogueira-Neto et al, 2013); evaluation of respiratory muscle work (Sarlabous et al, 2014); changes in MU activation strategies, which can occur with aging, neuromuscular diseases, endurance training programs, and care of injuries (Cooper et al, 2014); and Parkinson's disease (Marusiak et al, 2009;Malek and Coburn, 2012). In applications with comparisons between the MMG signal and the force response the biceps brachii (Orizio et al, 1989) and rectus femoris (Krueger et al, 2016;Shin et al, 2016) are the muscles more used due its easy accessibility and comparison capability.…”
Section: Introductionmentioning
confidence: 99%